Nutrition knowledge is associated with energy availability and carbohydrate intake in young female cross-country skiers - Kettunen, O.; Heikkilä, M.; Linnamo, V.; Ihalainen, J. K. (Nutrients, 2021)
The aim of this study was to provide information on energy availability (EA), macronutrient intake, nutritional periodization practices, and nutrition knowledge in young female cross-country skiers. A total of 19 skiers filled in weighted food and training logs before and during a training camp. Nutrition knowledge was assessed via a validated questionnaire. EA was optimal in 11% of athletes at home (mean 33.7 ± 9.6 kcal·kgFFM-1·d-1) and in 42% at camp (mean 40.3 ± 17.3 kcal·kgFFM-1·d-1). Most athletes (74%) failed to meet recommendations for carbohydrate intake at home (mean 5.0 ± 1.2 g·kg-1·d-1) and 63% failed to do so at camp (mean 7.1 ± 1.6 g·kg-1·d-1). The lower threshold of the pre-exercise carbohydrate recommendations was met by 58% and 89% of athletes while percentages were 26% and 89% within 1 h after exercise, at home and at camp, respectively. None of the athletes met the recommendations within 4 h after exercise. Nutrition knowledge was associated with EA at home (r = 0.52, p = 0.023), and with daily carbohydrate intake at home (r = 0.62, p = 0.005) and at camp (r = 0.52, p = 0.023). Carbohydrate intake within 1 and 4 h post-exercise at home was associated with better nutrition knowledge (r = 0.65, p = 0.003; r = 0.53, p = 0.019, respectively). In conclusion, young female cross-county skiers had difficulties meeting recommendations for optimal EA and carbohydrate intake. Better nutrition knowledge may help young athletes to meet these recommendations.